In Transit: The Well-Being of Migrants from Transition and Post-Transition Countries - Milena Nikolova; Carol Lee Graham (Institute for the Study of Labor (IZA), 2014)
The extant literature has focused on migration's consequences for the receiving countries. In this paper, we ask a different but important question: how much do migrants gain from moving to another country? Using Gallup World Poll data and a methodology combining statistical matching with difference-in-differences, we assess migration's effects on the well-being of migrants from transition economies. We contribute to the literature by showing that in addition to increasing household income, migration enhances subjective well-being and satisfaction with freedom. The results are robust to sensitivity checks. Understanding the causal effects of migration on perceived and actual well-being is crucial for an informed public policy debate and has direct implications for social cohesion and integration policy.
Keywords: F22; I31; J61; O15; 330; migration; transition economies; subjective well-being